ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI DAN PENGGUNAAN SISTEM INFORMASI PADA PASAR SWALAYAN (HYPERMARKET, SUPERMARKET DAN MINIMARKET) YANG TERDAFTAR DI JAKARTA - Rossje V. Suryaputri; Adi Widjanarko (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2012)
This study aimed to analyze the factors that affect the interest of information systems and use of information systems in Supermarkets are using five factors: (1) Performance Expectations, (2) Expectations Enterprises, (3) Social factors, (4) Interest Utilization and information systems (5) The conditions that facilitate users. This study took a sample of 60 Supermarket registered in Jakarta with convenience sampling method. Results of this study prove that performance expectations have an influence on the interest of information systems, while expectations of business and Ssocial factors has no effect on the interest of information systems. While interest in the utilization of information systems and conditions that facilitate the user has an influence on the use of information systems.Keywords: performance expectations, expectations of business and social factors.